2011
DOI: 10.1097/aci.0b013e32834c233a
|View full text |Cite
|
Sign up to set email alerts
|

T-cell receptor excision circles in primary immunodeficiencies and other T-cell immune disorders

Abstract: Confounding factors, such as cell division, cell death, longevity of the naïve T cells, and intracellular degradation, are known to affect TREC levels, yet measurement of TREC content is still considered the most reliable tool for tracking recent thymic emigrants. Its recent implantation for neonatal screening to diagnose severe combined immunodeficiency by using dry blood spots from Guthrie papers makes TREC the most accurate noninvasive tool to detect T-cell immune disorders. Together with determination of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 54 publications
0
31
0
1
Order By: Relevance
“…Our results indicate that these markers can be used to accurately estimate different intra-thymic capacities for assessing T cell function. TREC, a thymus by-product which quantifies recent thymic emigrants, is extensively used to assess primary T cell immunodeficiency and other processes in which T cell immunity is disrupted, including HIV, aging, bone marrow transplantation and others [18]. Arellano et al [17] have shown that, indeed, peripheral TREC levels well reflect thymic function and stable analytes, as demonstrated by their correlation with intra-thymic TREC values.…”
Section: Discussionmentioning
confidence: 97%
“…Our results indicate that these markers can be used to accurately estimate different intra-thymic capacities for assessing T cell function. TREC, a thymus by-product which quantifies recent thymic emigrants, is extensively used to assess primary T cell immunodeficiency and other processes in which T cell immunity is disrupted, including HIV, aging, bone marrow transplantation and others [18]. Arellano et al [17] have shown that, indeed, peripheral TREC levels well reflect thymic function and stable analytes, as demonstrated by their correlation with intra-thymic TREC values.…”
Section: Discussionmentioning
confidence: 97%
“…Assays for the copy number of TRECs in peripheral blood are now conducted in clinical and research laboratories to monitor naïve T cells emigrating from the thymus (reviewed by [18, 22]). Detecting absence of TRECs in newborns by population-based screening of their routinely collected DBS permits early diagnosis of SCID from otherwise unsuspected and asymptomatic newborns, making possible prompt intervention to prevent severe infections and provide definitive treatment with optimal outcome [32].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other newborn conditions with low numbers of T cells are also revealed by TREC screening. Furthermore, later in life, serial measurement of TRECs by qPCR can be used to document the status of thymic production of T cells in a variety of patients, such as those who have undergone hematopoietic cell transplantation (HCT) or other interventions such as treatments for malignancy or HIV infection ([1, 5, 16] and reviewed by [17, 18]).…”
Section: Introductionmentioning
confidence: 99%
“…The disease is fatal unless prompt measures are taken at very early age. Hence, early diagnosis and intervention would improve the outcome [83]. In this regard, TREC was used for the first time as a screening tool by McGhee et al [84].…”
Section: T Cell Reconstitution After Hsct and T Cell Receptor Excimentioning
confidence: 99%
“…Currently, TREC has proven to be the best non-invasive, feasible screening tool for SCID and has been implemented clinically in the USA. TREC analysis will most likely become a worldwide screening tool for SCID [83]. …”
Section: T Cell Reconstitution After Hsct and T Cell Receptor Excimentioning
confidence: 99%